Mass printing technologies for technical applications - Willert, Andreas; Hammerschmidt, Jens; Baumann, Reinhard R. (University of Pardubice, 2011)
The increasing use of printing technologies for the manufacturing of sensors, electronic circuits, conductors, other functional layers, etc. is a trend in current manufacturing environments. Hence, printing technologies have been utilized as a tool to deposit certain amounts of functional material on various substrates to gain a new quality in regard to cost effectiveness and production volume. Most of the already presented approaches are lab-based – only a few are already in the market. In this paper, we elucidate how inkjet technology and machine development of large area manufacturing technology employed for the printing of functional layers with the aim of technical applications are utilised. We describe the workflow for the manufacturing of fully printed microsieves providing the functionality porosity to be integrated in applications of filtration. Another example given is the manufacturing of batteries based on printing techniques in a pilot production line, with a push button printed complementary and SMD-LEDs mounted during assembly.